The (In)Appropriateness of the WAR Metaphor in Response to SARS-CoV-2: A Rapid Analysis of Donald J. Trump's Rhetoric - Bates, Benjamin R. (Frontiers in Communication, 2020)
The virus SARS-CoV-2 and the disease it causes (COVID-19) are unfamiliar topics to most publics. One mechanism used by political leaders to make the strange and unfamiliar more understandable and familiar to their publics is using metaphor. In his responses to SARS-CoV-2, US President Donald Trump used the WAR metaphor to shape public understanding. In this analysis, I reveal how the entailments chosen by Trump to complete this metaphor lead to rhetorical incoherence and undermine policy response to SARS-CoV02. I conclude with a call to reject WAR as a metaphor for understanding SARS-CoV-2 and COVID-19 and, instead, encourage adopting alternative metaphors to shape public understanding.